Teacher Competency Development In The Digital Era - Oktarina, Henny; Kristiawan, Muhammad; Martha, Alfroki (Jurnal Pendidikan Tambusai, 2021)
In this digital era, new technologies have emerged, resulting in extraordinary changes in all fields, including education. The increasing sophistication of technology, the heavier the demands for the competence of teachers. For this reason, at this time required the will and ability of teachers to understand the dynamics of the classroom in order to educate students well. This paper aims to describe the development of teacher competencies in the digital era. The method used is literature study with descriptive analysis techniques. The results showed a change in the educational paradigm. One of them is that teachers as educational actors must be able to improve and develop their competence in pedagogic, social, personality and professional aspects. This can be seen in the ability to communicate and collaborate, the ability to think critically and solve problems, the ability to emphasize conceptual learning, and the ability to use technology-based learning media.